Diabetes and Diabetic Foot Ulcers: An often hidden problem - Bronwyn Green; Andy Zoepke (South African Family Practice)
Diabetes affects an estimated 16 million people in the United States and only just over half of whom are aware they have the disease. It is one of the leading causes of disease-related deaths in the U.S. Diabetes and its related complications claim the lives of approximately 190,000 Americans annually. In South Africa the situation is just as dire with between 4 - 6 million people having Diabetes. “Diabetes Mellitus” represents a group of chronic diseases characterised by high levels of glucose in the blood and when the body does not produce enough insulin, or doesn’t produce insulin effectively. Insulin is a hormone necessary for the metabolism of sugar, starches and other foods. As a result, blood sugar rises far above normal levels and over time begins to damage organs and tissues. Diabetic patients, both type 1 and type 2, are at significant risk for a number of health complications associated with the eyes, feet, heart, blood vessels and the kidneys.